Efektivitas pendidikan multikultural dalam penguatan toleransi dan pluralisme mahasiswa di indonesia - Jannah, Nisa Ummul (Maliki Interdisciplinary Journal, 2026)
Multicultural education is an important educational approach for fostering religious tolerance and moderation in Indonesia’s diverse society. This study aims to analyze the effectiveness of multicultural education in strengthening religious tolerance and moderation among university students in Indonesia. This study employs a literature review method by analyzing various scientific journals related to multicultural education, religious moderation, and civic education. The results indicate that multicultural education can enhance attitudes of tolerance, democracy, cooperation, and respect for cultural and religious diversity. Furthermore, strengthening religious moderation through education can foster balanced religious attitudes and respect for differing beliefs. Civic education also plays a crucial role in enhancing students’ social awareness, critical thinking skills, and sense of national responsibility. Thus, the integration of multicultural education, religious moderation, and civic education serves as an effective strategy for maintaining national unity in Indonesia in the modern era.